2019
DOI: 10.1002/joc.6177
|View full text |Cite
|
Sign up to set email alerts
|

A new homogenized daily data set for temperature variability assessment in Italy

Abstract: We present a new data set of quality‐controlled and homogenized daily maximum (Tmax) and minimum (Tmin) temperature for Italy. The data set includes 144 Tmax and 139 Tmin long‐term series, covering the period 1961–2017. First, the paper provides a description of data sources and quality controls implemented for the detection of erroneous daily observations. Next, the temperature records used for this work are introduced. Following strict data continuity and completeness requirements, we identified more than 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
2
21
0
1
Order By: Relevance
“…In particular, in this paper, the Climatol package provided under the R programming language was applied because this method, by performing an iterative procedure, allows us to automatically identify and remove inhomogeneities from the series. Moreover, although it is acknowledged that homogenization methods cannot provide the real adjustment for artificial discontinuities affecting a climate time series, the efficiency of Climatol has been documented in several papers, also when compared to several other methods [23,38]. Finally, as pointed out by Fioravanti et al [38] the choice of automatic methods is required when there is a high number of weather stations and a lack of metadata documenting potential change points.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in this paper, the Climatol package provided under the R programming language was applied because this method, by performing an iterative procedure, allows us to automatically identify and remove inhomogeneities from the series. Moreover, although it is acknowledged that homogenization methods cannot provide the real adjustment for artificial discontinuities affecting a climate time series, the efficiency of Climatol has been documented in several papers, also when compared to several other methods [23,38]. Finally, as pointed out by Fioravanti et al [38] the choice of automatic methods is required when there is a high number of weather stations and a lack of metadata documenting potential change points.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Moreover, although it is acknowledged that homogenization methods cannot provide the real adjustment for artificial discontinuities affecting a climate time series, the efficiency of Climatol has been documented in several papers, also when compared to several other methods [23,38]. Finally, as pointed out by Fioravanti et al [38] the choice of automatic methods is required when there is a high number of weather stations and a lack of metadata documenting potential change points. The results of the homogenization procedures allowed us to detect that more than 50% of monthly rainfall series resulted as homogeneous.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…a region whose climate system will be particularly responsive to global change) (Giorgi, 2006). Significant increase in warm temperature indices and decrease in cold ones was already detected all over the Mediterranean region (Burić et al, 2015;Espirito Santo et al, 2014;Fernández-Montes & Rodrigo, 2012;Fioravanti et al, 2016;Fonseca et al, 2016;Kioutsioukis et al, 2010). In contrast to the consistent warming trends globally reported for the extreme temperature indices, most of the extreme precipitation indices (e.g.…”
mentioning
confidence: 96%
“…регион у којем ће климатски систем посебно реаговати на глобалне промјене) (Giorgi, 2006). Значајно повећање топлих температурних индекса и смањење хладних већ је забиљежено широм региона Медитерана (Burić et al, 2015;Espirito Santo et al, 2014;Fernández-Montes & Rodrigo, 2012;Fioravanti et al, 2016;Fonseca et al, 2016;Kioutsioukis et al, 2010). За разлику од конзистентног тренда загријавања који је глобално установљен за екстремне температуре, већина утврђених трендова индекса екстремних падавина (нпр.…”
unclassified
“…The reduction of standard deviation (due to the removal of step-like changes) and the increase of mutual correlation that is observed Mamara et al [2014] have confirmed the trustworthy of the homogenized dataset. The improved features of the networks have also been seen in the better spatial consistency of the trends [Syrakova and Stefanova, 2009;Hannart et al, 2014;Delvaux et al, 2018;Osadchyi et al, 2018;Yosef et al, 2018;Fioravanti et al, 2019] and in the removal of the anomalous ones [Vincent et al, 2002;Mamara et al, 2014;Pérez-Zanón et al, 2015; as can be seen in Figure 1.8. [Lawrimore et al, 2011], calculated with the method by [Menne and Williams Jr, 2009] Figure 1.8: Trends on TX90p over Austria after (left) and before (right) the homogenization.…”
Section: Effects Of the Homogenizationmentioning
confidence: 82%